A boron halide solid electrolyte suitable for high voltage, and a preparation method and application thereof

CN123018110APending Publication Date: 2026-10-30UNIV OF CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611407355.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-11
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0004]然而,现有卤化物固态电解质在高电压条件下仍存在稳定性不足的问题

Benefits of technology

[0023]其一,高离子电导率。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123018110A_ABST
    Figure CN123018110A_ABST
Patent Text Reader

Abstract

The application provides a boron halide solid electrolyte suitable for high voltage and a preparation method and application thereof. The boron halide solid electrolyte has a general chemical formula of Li a B b M c O m X n ; M is at least one of Mg, Al, Ga, Y, Sc, Y, In, Cr, La, Ce, V, Sm, Ti, Zr, Sn, Ge, Bi, Hf, Ho, Sb, Nb, Ta, W or Mo elements, X is a halogen element, 0
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of electrochemical energy storage materials technology, and relates to a boron halide solid electrolyte, its preparation method and application. Background Technology

[0002] With the rapid growth of global energy storage demand, all-solid-state batteries are considered an important development direction for next-generation energy storage batteries due to their advantages such as high energy density and good safety. As the core component of all-solid-state batteries, the solid electrolyte's ionic conductivity, electrochemical stability, and mechanical properties directly affect the energy density, cycle life, and safety performance of all-solid-state batteries.

[0003] Currently, solid electrolytes mainly include oxide, sulfide, polymer, and halide systems. Among them, halide solid electrolytes have high lithium-ion conductivity, good mechanical deformation capability, and good high-voltage stability, and have good compatibility with high-voltage cathode materials, thus showing great application potential in high-voltage all-solid-state lithium batteries.

[0004] However, existing halide solid electrolytes still suffer from insufficient stability under high-voltage conditions. When the charging cutoff voltage of an all-solid-state battery exceeds 4.3 V, chloride ions in the halide solid electrolyte are prone to oxidation under high potential, which may trigger interfacial side reactions between the solid electrolyte and the cathode material. This leads to increased interfacial impedance, resulting in battery capacity decay and decreased cycle stability, thus limiting the practical application of halide solid electrolytes in high-voltage all-solid-state batteries. Current methods to improve the high-voltage stability of solid electrolytes involve introducing fluorine-containing compounds (LiF) to enhance their high-voltage stability. However, the high electronegativity of fluorine leads to a significant decrease in lithium-ion conductivity, making practical application difficult.

[0005] Therefore, it is necessary to provide a novel halide solid electrolyte with high ionic conductivity and excellent high voltage stability to reduce the oxidative decomposition of the electrolyte and interfacial side reactions under high voltage conditions, and improve the cycle stability and service life of all-solid-state batteries. Summary of the Invention

[0006] The purpose of this invention is to overcome the aforementioned shortcomings of the prior art and provide a boron halide solid electrolyte, its preparation method, and its applications. The boron halide solid electrolyte exhibits high lithium-ion conductivity and good high-voltage stability, and can reduce the oxidative decomposition and interfacial side reactions of solid electrolytes under high-voltage conditions, thereby improving the cycle stability of all-solid-state lithium batteries.

[0007] To achieve the above-mentioned objectives, the present invention adopts the following technical solution:

[0008] In a first aspect, the present invention provides a boron halide solid electrolyte suitable for high voltage, wherein the boron halide solid electrolyte has the general chemical formula: Li a B b M c O m X n ;

[0009] Wherein, M is at least one of the elements Mg, Al, Ga, Y, Sc, Y, In, Cr, La, Ce, V, Sm, Ti, Zr, Sn, Ge, Bi, Hf, Ho, Sb, Nb, Ta, W, or Mo; X is a halogen element, and at least one of the elements F, Cl, Br, or I; 0 <a≤6;0<b≤3; 0<c≤2; 0<m≤6; 0<n≤10。

[0010] The boron halide provided by this invention has a special local structure (BO3 / BO4 unit), which makes the material stable under high pressure, while the diverse coordination conditions can ensure the ionic conductivity of the solid electrolyte.

[0011] Secondly, the present invention provides a method for preparing the boron halide solid electrolyte described above, the method comprising:

[0012] After mixing the lithium source, M source and X source, the mixture is subjected to high-energy ball milling (or pulverizing) to obtain the boron halide solid electrolyte.

[0013] Preferably, the lithium source is at least one of Li2B4O7, LiBO2, Li3BO3 or LiBF4;

[0014] Preferably, the M source is at least one of the halides of M;

[0015] Preferably, the X source is at least one of LiX or MX.

[0016] Preferably, in the high-energy ball mill, the mass ratio of the milling beads to the reactants is (1-80):1.

[0017] Preferably, the high-energy ball mill operates at a speed of 200–900 rpm.

[0018] Preferably, the high-energy ball milling time is 0.5 to 48 hours.

[0019] Preferably, the atmosphere of the high-energy ball mill is an inert atmosphere, and the gas in the inert atmosphere is at least one of nitrogen, argon or neon.

[0020] Preferably, the high-energy ball mill equipment includes any one or a combination of at least two of the following: a high-energy ball mill, a vibrating ball mill, or a sand mill.

[0021] Thirdly, the present invention also provides an application of the boron halide solid electrolyte in lithium-ion batteries. The solid electrolyte of the present invention can be used as a solid electrolyte layer, a positive electrode coating material, and a positive electrode composite electrode, and can be used in conjunction with high-voltage positive electrode materials such as high-nickel layered oxides and lithium-rich manganese-based oxides.

[0022] Compared with the prior art, the present invention has the following main advantages:

[0023] First, high ionic conductivity.

[0024] This invention introduces boron and oxygen-containing components into a halide solid electrolyte system to regulate the local chemical environment and structural characteristics of the solid electrolyte, which is conducive to the formation of a disordered structure suitable for lithium-ion migration, thereby obtaining a higher lithium-ion conductivity.

[0025] Secondly, it has good high voltage stability.

[0026] The boron halide solid electrolyte provided by this invention can reduce the tendency of electrolyte to undergo oxidative decomposition under high potential conditions and improve the interfacial stability between the solid electrolyte and the high-voltage positive electrode, thus making it suitable for high-voltage all-solid-state lithium-ion batteries.

[0027] Third, amorphous structures are advantageous for ion transport.

[0028] The solid electrolyte of the present invention is preferably prepared by high-energy ball milling, which can destroy the crystal structure of the raw material and form an amorphous phase or a structure dominated by the amorphous phase under mechanochemical action, thereby reducing the restriction of lithium ion migration by grain boundaries.

[0029] Fourth, the preparation process is simple.

[0030] This invention uses a high-energy ball milling method to prepare solid electrolytes, which does not require a complex high-temperature sintering process, and the preparation process is simple and has good process adaptability.

[0031] Fifth, it is suitable for high-voltage all-solid-state batteries. Attached Figure Description

[0032] Figure 1 The X-ray diffraction pattern of the boron halide solid electrolyte Li3BTaO3Cl5 provided in Example 1 of this invention.

[0033] Figure 2 The X-ray diffraction pattern of the boron halide solid electrolyte Li2B2TaO4Cl5F4 provided in Example 4 of the present invention.

[0034] Figure 3 EIS impedance diagram of Li3BTaO3Cl5 solid electrolyte provided in Example 1 of this invention.

[0035] Figure 4 EIS impedance diagram of Li2B2ZrO4Cl4 solid electrolyte provided in Example 7 of the present invention.

[0036] Figure 5 A scanning electron microscope (SEM) image of the boron halide solid electrolyte Li3BTaO3Cl5 provided in Example 1 of this invention.

[0037] Figure 6 This refers to the all-solid-state lithium metal battery NCM90|Li6B2TaO6Cl5|Li6PS5Cl|LiIn provided in Embodiment 11 of the present invention. 1.3 Figure showing the results of the cycling performance test under 5C rate conditions.

[0038] Figure 7 This refers to the Li6B2TaO6Cl5 solid electrolyte provided in Example 11 of the present invention. 11 B-Solid NMR image. Detailed Implementation

[0039] The technical solution of the present invention will be further described below through specific embodiments and accompanying drawings.

[0040] Example 1:

[0041] This embodiment provides a boron halide solid electrolyte with the chemical formula Li3BTaO3Cl5.

[0042] This embodiment also provides a method for preparing the above-mentioned boron halide solid electrolyte, the preparation method comprising:

[0043] In an atmosphere filled with Ar gas, Li3BO3 and TaCl5 were mixed at a stoichiometric ratio of 1:1 and then ball-milled at 500 rpm for 36 hours in a high-energy ball mill. The mass ratio of the ball mill beads to the reactants was 40:1, yielding Li3BTaO3Cl5 boron halide solid electrolyte.

[0044] The X-ray diffraction pattern of the Li3BTaO3Cl5 boron halide solid electrolyte prepared in Example 1 is shown below. Figure 1 As shown. From Figure 1 As can be seen, no diffraction peaks were observed, indicating that the Li3BTaO3Cl5 boron halide solid electrolyte is completely amorphous. The Li3BTaO3Cl5 boron halide solid electrolyte prepared in Example 1 was subjected to AC impedance testing using an electrochemical workstation. The test results are as follows: Figure 3 As shown in the figure. Calculations based on the test results indicate that the ionic conductivity of the boron halide solid electrolyte prepared in Example 1 at room temperature is 1.82 × 10⁻⁶. -3S / cm. The scanning image of the Li3BTaO3Cl5 boron halide solid electrolyte prepared in Example 1 is shown below. Figure 5 As shown. From Figure 5 As can be seen, the synthesized electrolyte powder consists of irregular particles with a particle size of less than 10 μm.

[0045] Example 2:

[0046] This embodiment provides a boron halide solid electrolyte with the chemical formula LiB₂TaO. 3.5 Cl5.

[0047] This embodiment also provides a method for preparing the above-mentioned boron halide solid electrolyte, the preparation method comprising:

[0048] In an Ar atmosphere, Li₂B₄O₇ and TaCl₅ were mixed at a stoichiometric ratio of 0.5:1 and then ball-milled at 700 rpm for 24 hours in a high-energy ball mill. The mass ratio of milling beads to reactants was 20:1, yielding LiB₂TaO₇. 3.5 Cl5 boron halide solid electrolyte.

[0049] Example 3:

[0050] This embodiment provides a boron halide solid electrolyte with the chemical formula Li₂B₂TaO₄Cl₅.

[0051] This embodiment also provides a method for preparing the above-mentioned boron halide solid electrolyte, the preparation method comprising:

[0052] In an atmosphere filled with N2 gas, LiBO2 and TaCl5 were mixed at a stoichiometric ratio of 2:1 and then ball-milled at 900 rpm for 12 hours in a high-energy ball mill. The mass ratio of the milling beads to the reactants was 10:1, yielding Li2B2TaO4Cl5 boron halide solid electrolyte.

[0053] Example 4:

[0054] This embodiment provides a boron halide solid electrolyte with the chemical formula Li4B2TaO3Cl5F4.

[0055] This embodiment also provides a method for preparing the above-mentioned boron halide solid electrolyte, the preparation method comprising:

[0056] In an atmosphere filled with Ar gas, LiBF4, Li3BO3 and TaCl5 were mixed in a stoichiometric ratio of 1:1:1 and then ball-milled in a high-energy ball mill at 600 rpm for 20 h. The mass ratio of the ball mill beads to the reactants was 15:1, yielding a Li2B2TaO4Cl5F4 boron halide solid electrolyte.

[0057] The X-ray diffraction pattern of the Li4B2TaO3Cl5F4 boron halide solid electrolyte prepared in Example 4 is shown below. Figure 2 As shown. Figure 2 It can be seen that there are diffraction characteristic peaks at diffraction angles 2θ of 15.1°, 16.5°, 19.7°, 29.4°, 32.6°, 34.0°, 38.3°, 42.3°, 50.6° and 62.0°, but the crystallinity is not high and it is still dominated by the amorphous phase.

[0058] Example 5:

[0059] This embodiment provides a boron halide solid electrolyte with the chemical formula Li. 4.5 B 1.5 NbO 4.5 Cl5.

[0060] This embodiment also provides a method for preparing the above-mentioned boron halide solid electrolyte, the preparation method comprising:

[0061] In an Ar atmosphere, Li3BO3 and NbCl5 were mixed at a stoichiometric ratio of 1.5:1 and then ball-milled at 700 rpm for 20 hours in a high-energy ball mill. The mass ratio of milling beads to reactants was 10:1, yielding Li. 4.5 B 1.5 NbO 4.5 Cl5 boron halide solid electrolyte.

[0062] Example 6:

[0063] This embodiment provides a boron halide solid electrolyte with the chemical formula Li3BAlO3Cl3.

[0064] This embodiment also provides a method for preparing the above-mentioned boron halide solid electrolyte, the preparation method comprising:

[0065] In an atmosphere filled with Ar gas, Li3BO3 and AlCl3 were mixed at a stoichiometric ratio of 1:1 and then ball-milled at 900 rpm for 2 hours in a high-energy ball mill. The mass ratio of the ball mill beads to the reactants was 80:1, yielding Li3BAlO3Cl3 boron halide solid electrolyte.

[0066] Example 7:

[0067] This embodiment provides a boron halide solid electrolyte with the chemical formula Li₂B₂ZrO₄Cl₄.

[0068] This embodiment also provides a method for preparing the above-mentioned boron halide solid electrolyte, the preparation method comprising:

[0069] In an atmosphere filled with Ar gas, LiBO2 and ZrCl4 were mixed at a stoichiometric ratio of 2:1 and then ball-milled at 800 rpm for 30 h in a high-energy ball mill. The mass ratio of the ball mill beads to the reactants was 50:1, yielding a Li2B2ZrO4Cl4 boron halide solid electrolyte.

[0070] The Li₂B₂ZrO₄Cl₄ boron halide solid electrolyte prepared in Example 7 was subjected to AC impedance testing using an electrochemical workstation. The test results are as follows: Figure 4 As shown in the figure. Based on the test results, the ionic conductivity of the boron halide solid electrolyte prepared in Example 7 at room temperature is 4.15 × 10⁻⁶. -3 S / cm.

[0071] Example 8:

[0072] This embodiment provides a boron halide solid electrolyte with the chemical formula Li3BTaY. 0.3 O3Cl5F 0.9 .

[0073] This embodiment also provides a method for preparing the above-mentioned boron halide solid electrolyte, the preparation method comprising:

[0074] In an Ar atmosphere, Li3BO3, TaCl5, and YF3 were mixed in a stoichiometric ratio of 1:1:0.3 and then ball-milled at 800 rpm for 20 hours in a high-energy ball mill. The mass ratio of milling beads to reactants was 15:1, yielding Li3BTaY. 0.3 O3Cl5F 0.9 Boron halide solid electrolytes.

[0075] Example 9:

[0076] This embodiment provides a boron halide solid electrolyte with the chemical formula Li3BTaMg. 0.1 O3Cl5F 0.2 .

[0077] This embodiment also provides a method for preparing the above-mentioned boron halide solid electrolyte, the preparation method comprising:

[0078] In an Ar atmosphere, Li3BO3, TaCl5, and MgF2 were mixed in a stoichiometric ratio of 1:1:0.1 and then ball-milled at 800 rpm for 20 hours in a high-energy ball mill. The mass ratio of milling beads to reactants was 15:1, yielding Li3BTaMg. 0.1 O3Cl5F 0.2 Boron halide solid electrolyte.

[0079] Example 10:

[0080] The difference between this embodiment and Example 1 is that the molar ratio of Li3BO3 to TaCl5 is adjusted to 1.5:1, resulting in a final solid electrolyte with the chemical formula Li. 4.5 B 1.5 TaO 4.5 Cl5.

[0081] The remaining parameters are exactly the same as in Example 1.

[0082] Example 11:

[0083] The difference between this embodiment and Example 1 is that the molar ratio of Li3BO3 to TaCl5 is adjusted to 2:1, so that the final solid electrolyte has the chemical formula Li6B2TaO6Cl5.

[0084] The remaining parameters are exactly the same as in Example 1.

[0085] The nickel-cobalt-manganese ternary cathode NCM90, Li6B2TaO6Cl5, and VGCF were thoroughly mixed at a mass ratio of 70:30:1 to obtain a composite cathode. 80 mg of Li6B2TaO6Cl5 was evenly sprinkled into a PEEK mold and compacted under 2 tons of pressure. 80 mg of Li6PS5Cl was sprinkled on one side of the Li6B2TaO6Cl5 and compacted under 1.5 tons of pressure. Approximately 8 mg of the composite cathode was evenly spread on the LIC side and pressed under 2 tons of pressure for 5 minutes. Finally, the composite anode LiIn was... 1.3 Cut 10mm round pieces, attach them to the surface of Li6PS5Cl, and seal them to obtain an all-solid-state lithium metal battery NCM90|Li6B2TaO6Cl5|Li6PS5Cl|LiIn 1.3 The battery cycle performance was tested, and the results are as follows: Figure 6 As shown.

[0086] Figure 6 The all-solid-state lithium metal battery NCM90|Li6B2TaO6Cl5|Li6PS5Cl|LiIn provided in Embodiment 11 of this invention 1.3 The graph shows the cycling performance test results under 5C rate conditions, specifically the changes in specific capacity and coulombic efficiency. Figure 6 It can be seen that NCM90|Li6B2TaO6Cl5|Li6PS5Cl|LiIn 1.3 With a positive electrode active material loading of 7 mg·cm³ -2 Under conditions of 5C rate and 4.5V charging cutoff voltage, the capacity retention was 100% after 200 cycles without any short circuit, demonstrating extremely excellent high-voltage cycling stability. The Li6B2TaO6Cl5 boron halide solid electrolyte prepared in Example 11... 11B solid-state NMR images, such as Figure 7 As shown. From Figure 7 It can be seen that solid electrolytes contain BO3 and BO4 units that can improve electron distribution, which is the fundamental reason why solid electrolytes can withstand high voltage.

[0087] The above description is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention fall within the protection and disclosure scope of the present invention.

Claims

1. A boron halide solid electrolyte suitable for high voltage, characterized in that, The general chemical formula of the boron halide solid electrolyte is: Li a B b M c O m X n ; Wherein, M is at least one of the elements Mg, Al, Ga, Y, Sc, Y, In, Cr, La, Ce, V, Sm, Ti, Zr, Sn, Ge, Bi, Hf, Ho, Sb, Nb, Ta, W, or Mo; X is a halogen element; 0 <a≤6;0<b≤3; 0<c≤2;0<m≤6;0<n≤10。 2. The boron halide solid electrolyte suitable for high voltage according to claim 1, characterized in that: X is at least one of the elements F, Cl, Br or I.

3. The boron halide solid electrolyte suitable for high voltage according to claim 1, characterized in that, The boron halide solid electrolyte is an amorphous phase or a composite structure containing an amorphous phase.

4. A method for preparing a boron halide solid electrolyte suitable for high voltage as described in any one of claims 1-3, characterized in that, The preparation method includes: The lithium source, M source and X source are mixed and then subjected to high-energy ball milling to obtain the boron halide solid electrolyte.

5. The preparation method according to claim 4, characterized in that, The lithium source is at least one of Li2B4O7, LiBO2, Li3BO3 or LiBF4; The M source is at least one of the halides of M; The X source is at least one of LiX or MX.

6. The preparation method according to claim 4, characterized in that, In the high-energy ball mill, the mass ratio of the milling beads to the reactants is (1-80):1; The high-energy ball mill rotates at a speed of 200–900 rpm; The high-energy ball milling time is 0.5–48 h; The atmosphere for the high-energy ball mill is an inert atmosphere, and the gas in the inert atmosphere is at least one of nitrogen, argon, or neon.

7. A lithium-ion battery, characterized in that, The lithium-ion battery includes the boron halide solid electrolyte as described in any one of claims 1-3.

8. The application of the boron halide solid electrolyte according to any one of claims 1-3 in a lithium-ion battery, characterized in that, The solid electrolyte is used in solid electrolyte layers, positive electrode composite materials, and / or positive electrode composite electrodes.